The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1108/sampj-10-2019-0365
|View full text |Cite
|
Sign up to set email alerts
|

Teaching sustainable development in business sciences degrees: evidence from Portugal

Abstract: Purpose This paper aims to analyze the current state of integration of sustainable development (SD), in the academic curricula of Business Sciences degrees, including matters about Ethics, Corporate Social Responsibility and Sustainability. In this way, the paper explores how Portuguese public higher education institutions (HEI) contribute to teaching about sustainable development (TSD). Design/methodology/approach The study focuses on Business Sciences degrees. The webpages of all public HEI with BSc and MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 77 publications
0
17
0
3
Order By: Relevance
“…One of these goals is to ensure that all students acquire the necessary knowledge and skills to promote sustainable development (UNESCO, 2017). According to this agenda, it is necessary to redesign education with the aim of integrating sustainable development principles and practices into all aspects of education and learning which lead to a development in knowledge, values and attitudes of the students and enabling them to promote the transition to sustainability and ensure a more sustainable and fair society for all (Gomes et al , 2021). Education, especially in accounting, is considered by many practitioners to be crucial in achieving sustainable development, and hence it is imperative that accounting education integrate sustainability issues (Hazelton and Haigh, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of these goals is to ensure that all students acquire the necessary knowledge and skills to promote sustainable development (UNESCO, 2017). According to this agenda, it is necessary to redesign education with the aim of integrating sustainable development principles and practices into all aspects of education and learning which lead to a development in knowledge, values and attitudes of the students and enabling them to promote the transition to sustainability and ensure a more sustainable and fair society for all (Gomes et al , 2021). Education, especially in accounting, is considered by many practitioners to be crucial in achieving sustainable development, and hence it is imperative that accounting education integrate sustainability issues (Hazelton and Haigh, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Section 4.2, we identify the phases of the method, and in Section 4.3 we present a detailed development of the method. Previous studies have found that bringing sustainability issues to the higher education curricula may lead to several positive outcomes related to attitudes and behavior [55], but it has also been found that the inclusion of this topic in accounting education is still uncoordinated and sporadic [53,54]. Furthermore, it has been noted that there are some resistances from academic staff in changing the teaching focus such as the combination of qualitative and quantitative information, to thinking long-term instead of only short-term, to teach strategy instead of only transactional [19,56].…”
Section: Discussionmentioning
confidence: 99%
“…Dumay and Adams [52] consider that one of the reasons why intellectual capital does not penetrate and proliferate in management practice is the discourse of academics. Also, the efforts to disseminate topics such as sustainability, sustainable development, social accounting, and environmental cost systems in accounting education seems to be uncoordinated and sporadic with space for improvement [53,54]. However, Lee, Birkey, and Patten [55] show that bringing sustainability issues to the accounting curriculum can lead to positive student outcomes in terms of attitude, perceived behavioral control, intentions, and behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, the last paper in this special issue explores teaching sustainable development in business sciences degrees. Based on evidence from Portugal, Gomes et al (2020) analyzed the current state of integration of sustainable development in the academic curricula of business sciences degrees, including matters about ethics, CSR and sustainability. In this way, the paper explored how Portuguese public higher education institutions contribute to teaching on sustainable development.…”
Section: Content Of the Special Issuementioning
confidence: 99%